Post expansion evaluation of the midpalatal suture in children submitted to rapid palatal expansion: A CT study - Da Silva Filho, Omar Gabriel; Lara, Tulio Silva [UNESP]; Da Silva, Helena Cristina; Bertoz, Francisco Antônio (My University, 2006)
The aim of this prospective study was to evalute the midpalatal suture in children submitted to rapid palatal expansion, at the end of the retention stage, with CT scans. The sample was comprised of 17 children aged between 5 years 2 months and 10 years 5 months. The tomographic images showed that the midpalatal suture was completely ossified from the anterior nasal spine area to the posterior nasal spine area at the end of the retention phase, that is, 8 to 9 months post-expansion.
Keywords: Orthodontics; Palatal expansion technique; Suture; Tomography; bone development; child; computer assisted tomography; cranial suture; female; hard palate; human; male; maxilla; nasal bone; nose cavity; orthodontics; physiology; preschool child; prospective study; radiography; three dimensional imaging; Child; Child, Preschool; Cranial Sutures; Female; Humans; Imaging, Three-Dimensional; Male; Maxilla; Nasal Bone; Nasal Cavity; Osteogenesis; Palatal Expansion Technique; Palate, Hard; Prospective Studies; Tomography, X-Ray Computed